"Análisis de la incidencia de la eliminación del subsidio al gas doméstico en el ingreso y gasto de las familias ecuatorianas" - Amoroso Gavidia, Gisela Estefanía (2016)
The purpose of this research is to evaluate the impact of a possible elimination of the cooking gas subsidy in Ecuador and it possible effects on family income and expenses using the “Lorenzo Curve” and Gini Coefficient. Information from the National Survey of Income and Expenditure Survey Urban and Rural (ENIGUR) (2012) will be used since it contains more accurate and current data on the income and expenses of Ecuadorian families especially spending on LPG (gas). The research study will be presented in four chapters. Chapter One will present the research goals and objectives and the significance of the study. Chapter Two will present the theoretical foundations of the research, comparative findings in other countries such as Mexico, Peru, and Columbia, and presentation of the research variables and research hypotheses. Chapter Three will present the methodological framework of the research and mathematical models relative to the research objectives. Chapter Four will present the research study conclusions and recommendations regarding the possible elimination of the cooking gas subsidy in Ecuador and it possible effects on family income and expenses.